ANALISIS PERENCANAAN TEBAL JENIS LAPIS PERMUKAAN TAMBAHAN (OVERLAY) JALAN KABUPATEN DENGAN METODE BINA MARGA 2017 - Sri Indah Susanti; Adi Subandi; Endang Setiadi Permana (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2022)
Roads are one of the important infrastructures for connecting various places such as industrial centers, agricultural land, settlements and as a means of distributing goods and services to support the economy. With the increasing growth of vehicles, both in terms of number and load capacity being transported, it causes damage to the road surface and road pavement structure. One of the efforts to avoid serious road damage is to add a layer of pavement. The purpose of planning to increase the layer thickness is to restore the strength of the pavement so that it can provide optimal service to road users. In connection with the above problems, of course using an effective and efficient method. To plan the thickness in order to obtain good results. Based on the description above, the author is interested in discussing the analysis of the thickness of the additional surface layer (overlay) with the 2017 Highways method on the Wanareja-Cibogo road section, Subang Regency. In this study, the thickness of the overlay (overlay) was calculated at 2.76 mm. The surface layer used is Laston, the AE18KSAL value is 10.98 x 106, so the allowable back-plan is 0.6 mm, so that the thickness of the pavement layer with an additional layer (Overlay) is 3 cm.